Alterations in energy production in a Drosophila model for the X-linked dystonia-parkinsonism-related Taf1 deficiency - Mandik, Frida; Algodon, Shela Marie; Seibler, Philip; Klein, Christine; Vos, Melissa (Frontiers in Aging Neuroscience, 2026)
BackgroundX-linked dystonia-parkinsonism (XDP), an adult-onset neurodegenerative disorder, is caused by an SVA insertion in the TAF1 gene, containing a hexanucleotide, the length of which is correlated to the severity of the disease. The SVA insertion moderately disrupts gene expression; however, the underlying disease mechanism remains enigmatic.MethodsHere, we characterized a fly model for Taf1 deficiency and performed a pilot RNA sequencing analysis. Subsequently, we validated these findings in Taf1-deficient flies and in XDP patient-derived fibroblasts.ResultsWe identified an upregulation of genes involved in lipid-dependent energy production as a compensatory mechanism to maintain proper ATP levels. However, studies in XDP patient-derived fibroblasts with minor TAF1 reduction did not confirm these findings.Conclusionβ-oxidation is elevated in flies with severe TAF1 reduction but not detected in XDP-patient fibroblasts, suggesting that this compensatory mechanism may only manifest above a critical TAF1 dosage threshold, absent in patient basal conditions. This finding thus suggests that dosage-dependent metabolic responses occur following TAF1 loss.